Colitis Induces Enteric Neurogenesis Through a 5-HT4–dependent Mechanism. Issue 4 (April 2015) - Belkind-Gerson, Jaime; Hotta, Ryo; Nagy, Nandor; Thomas, Alyssa R.; Graham, Hannah; Cheng, Lily; Solorzano, Juan; Nguyen, Deanna; Kamionek, Michal; Dietrich, Jorg; Cherayil, Bobby J.; Goldstein, Allan M.
Abstract : Background: The intestine is known to contain enteric neuronal progenitors, but their precise identity and the mechanisms that activate them remain unknown. Based on the evidence for the neurogenic role of serotonin (5-HT) in the postnatal gut and the observation of enteric neuronal hyperplasia in inflammatory bowel disease, we hypothesized that colitis induces a neurogenic response through 5-HT4 receptor signaling. Methods: We examined the effects of 5-HT4 agonism on colonic neurogenesis and gliogenesis in vitro and in vivo in adult mice using dextran sodium sulfate to experimentally induce colitis. Results: In vitro, 5-HT4 agonism led to increased neuronal proliferation and density. Induction of experimental colitis in vivo similarly resulted in increased numbers of myenteric neurons, and this was inhibited by 5-HT4 antagonism. Interestingly, both in vitro and in vivo, 5-HT4 signaling increased glial cell proliferation but did not increase glial cell numbers, leading us to hypothesize that glia may give rise to neurons. After induction of colitis in normal, Nestin-GFP and Sox2-GFP transgenic mice, it was revealed that multiple glial markers (Sox2, Nestin, and CD49b) became strongly expressed by enteric neurons. Immunoselected enteric glia were found to give rise to neurons in culture, and this was inhibited in the presence of 5-HT4 blockade. Finally, isolated glia gave rise to a neuronal network upon transplantation into aganglionic embryonic avian hindgut. Conclusions: These results show that colitis promotes enteric neurogenesis in the adult colon through a serotonin-dependent mechanism that drives glial cells to transdifferentiate into neurons. Abstract : Article first published online 11 February 2015.